New caddisfly records (Insecta, Trichoptera) for Montenegro and Ecoregion 5, Dinaric Western Balkans: distributional and ecological insights - Hakan Bozdoğan; Astrit Bilalli; Halil Ibrahimi (Biodiversity Data Journal)
The level of knowledge about the caddisfly fauna of Montenegro remains limited compared to that of some other countries in the Balkan Peninsula due to fewer systematic studies and historical gaps in data collection.Adult caddisfly specimens were collected from the Zeta River in Montenegro during July and October 2024. Additionally, caddisfly data from Montenegro derived from a small, previously unprocessed collection of specimens collected in 2017 were included. Thirteen species belonging to six caddisfly families were identified. Three species are reported for the first time from Montenegro: Hydroptila angustata Mosely, 1939, Hydropsyche bulbifera McLachlan, 1878 and Potamophylax goulandriourum Malicky, 1974. All these three species are reported for the first time from Ecoregion 5, Dinaric Western Balkans. Additionally, a few other rarely recorded species in the Western Balkans, such as Hydropsyche modesta Navàs, 1925, Limnephilus graecus Schmid, 1965, Odontocerum albicorne (Scopoli, 1763) and Hydroptila sparsa Curtis, 1834, were documented. Notably, Limnephilus graecus was found during autumn, despite previously being reported only in spring and summer, suggesting a potential shift in its adult emergence patterns.These findings enhance our understanding of the distribution and diversity of several rare caddisfly species, particularly with the new records for Montenegro and Ecoregion 5, Dinaric Western Balkans. They underscore the critical need for further research and conservation efforts to support freshwater biodiversity in this region.